Deguelin’s Anticancer Bioactivity: Challenges and Opportunities in Medicinal Chemistry - Jiang, Wenjie; Zeng, Jing; Guo, Li; Shi, Jianyou; Lei, Yang (Frontiers in Pharmacology, 2025)
Deguelin is a natural isoflavone derived from the rotenone family, commonly found in plants belonging to the Derris and Grifola genera. Comprehensive research has underscored its considerable promise in oncological treatment. Deguelin demonstrates anticancer activity by suppressing cell proliferation and promoting apoptosis via the modulation of critical signaling pathways, such as NF-κB, Wnt, and AMPK pathways. Moreover, deguelin demonstrates several biological activities, including cell cycle arrest, autophagy modulation, anti-angiogenic and anti-metastatic capabilities, along with antioxidant and anti-inflammatory actions. Notwithstanding these encouraging benefits, the practical utilization of deguelin has been impeded by its volatility, possible neurotoxicity, and other detrimental consequences. This review initially examines the antitumor biological actions of deguelin, incorporating recent discoveries regarding its methods of action. It subsequently consolidates studies on structural alterations intended to enhance the efficacy of deguelin while mitigating its toxicity, and offers a summary of the structure-activity connections of its derivatives. The review seeks to further research on deguelin and guide the development of more efficacious derivatives for prospective clinical applications. This study seeks to establish a robust basis for the advancement of deguelin as a potential chemopreventive agent for cancer.